Abundance, not diversity, of host beetle communities determines abundance and diversity of parasitoids in deadwood. Issue 11 (8th April 2021) - Vogel, Sebastian; Prinzing, Andreas; Bußler, Heinz; Müller, Jörg; Schmidt, Stefan; Thorn, Simon
Abstract: Most parasites and parasitoids are adapted to overcome defense mechanisms of their specific hosts and hence colonize a narrow range of host species. Accordingly, an increase in host functional or phylogenetic dissimilarity is expected to increase the species diversity of parasitoids. However, the local diversity of parasitoids may be driven by the accessibility and detectability of hosts, both increasing with increasing host abundance. Yet, the relative importance of these two mechanisms remains unclear. We parallelly reared communities of saproxylic beetle as potential hosts and associated parasitoid Hymenoptera from experimentally felled trees. The dissimilarity of beetle communities was inferred from distances in seven functional traits and from their evolutionary ancestry. We tested the effect of host abundance, species richness, functional, and phylogenetic dissimilarities on the abundance, species richness, and Shannon diversity of parasitoids. Our results showed an increase of abundance, species richness, and Shannon diversity of parasitoids with increasing beetle abundance. Additionally, abundance of parasitoids increased with increasing species richness of beetles. However, functional and phylogenetic dissimilarity showed no effect on the diversity of parasitoids. Our results suggest that the local diversity of parasitoids, of ephemeral and hidden resources like saproxylic beetles, is highest when resources are abundant and thereby detectable and accessible. Hence, in some cases, resources do not need to be diverse to promote parasitoid diversity. Abstract : We investigated saproxylic beetles and parasitoid Hymenoptera reared from experimentally felled trees. We show that host diversity must not mandatory promote parasitoid diversity (pictures were used after the Creative Commons license (CC BY‐SA‐2.0 and CC BY‐3.0); copyright by U. Schmidt and M.A. Broussard).